KESESUAIAN LAHAN TANAMAN BUAH-BUAHAN DI AREA RENCANA PENGEMBANGAN AGROWISATA KECAMATAN LIKUPANG BARAT - Julio I. Luntungan; Karamoy L. Theffie; Zetly E. Tamod (COCOS, 2019)
ABSTRACT Awareness of health impacts through fruit consumption, demanded fruit yields to be always available, on the one hand the suitability of a plant requires different geographical conditions, this causes not all regions in Indonesia to produce various kinds of fruit. In land use planning, information of land potential is needed first, for specific use. This study aims to assess the actual and potential land suitability of mango (Mangifera indica),rambutan (Nephelium lappaceum), durian (Durio zibethinus), and passion fruit (Passiflora edulis) as well as to recommend suitable fruit plants to be cultivated in the study area. This research occurred in the plan area of agrotourism development PT. Bhineka Manca Wisata in Paputungan Village, West Likupang District, North Minahasa. Soil analysis was tested at the Soil Conservation Laboratory and Soil Fertility Laboratory, Department of Soil Science Faculty of Agriculture Sam Ratulangi University. The results showed the land with mixed forest land cover, has an actual land suitability class to mango, rambutan, durian, and passion fruit are marginally suitable. Whereas in the area of land covered by the bamboo forest, the actual suitability of the mango and passion fruit are marginally suitable, to rambutan and durian are moderately suitable. On land covered by shrubs, the actual land suitability class of mango, rambutan, durian, and passion fruit are marginally suitable. Keyword : Land suitability, fruits, agrotourism, West Likupang